High‐Efficiency Perovskite Light‐Emitting Diodes with Synergetic Outcoupling Enhancement - Shen, Yang; Cheng, Li‐Peng; Li, Yan‐Qing; Li, Wei; Chen, Jing‐De; Lee, Shuit‐Tong; Tang, Jian‐Xin (Advanced materials (Weinheim), 2019)
Perovskite light‐emitting diodes (PeLEDs) show great application potential in high‐quality flat‐panel displays and solid‐state lighting due to their steadily improved efficiency, tunable colors, narrow emission peak, and easy solution‐processing capability. However, because of high optical confinement and nonradiative charge recombination during electron–photon conversion, the highest reported efficiency of PeLEDs remains far behind that of their conventional counterparts, such as inorganic LEDs, organic LEDs, and quantum‐dot LEDs. Here a facile route is demonstrated by adopting bioinspired moth‐eye nanostructures at the front electrode/perovskite interface to enhance the outcoupling efficiency of waveguided light in PeLEDs. As a result, the maximum external quantum efficiency and current efficiency of the modified cesium lead bromide (CsPbBr3) green‐emitting PeLEDs are improved to 20.3% and 61.9 cd A−1, while retaining spectral and angular independence. Further reducing light loss in the substrate mode using a half‐ball lens, efficiencies of 28.2% and 88.7 cd A−1 are achieved, which represent the highest values reported to date for PeLEDs. These results represent a substantial step toward achieving practical applications of PeLEDs. Highly efficient perovskite light‐emitting diodes are achieved by implementing a simple and cost‐effective method for efficient outcoupling of waveguided light. A record external quantum efficiency of 28.2% is realized for the device based on cesium lead bromide (CsPbBr3), while retaining the same spectral response for broad viewing angles.